A research on effect of surface treatment conditions on flammability and water repellency properties of drapery fabrics produced from micro polyester yarns. Issue 2 (1st February 2021) - Karakan Günaydın, Gizem; Çeven, Erhan Kenan; Gürarda, Ayça; Akgün, Mine
Abstract: Flame retardancy and water repellency are frequently applied finishing processes for drapery fabrics. These two treatments should require special attention when they are applied consecutively. This research aims to investigate the effect of sequential finishing processes by utilizing of different flame retardant chemical ratio (0, 60 and 90 g/l) and fluorocarbon based water repelling substance ratio (0, 10 and 30 g/l) on hydrophobic, flammability, air permeability and stiffness properties of the drapery fabrics. According to the results of statistical analyses, it was determined that fabric burning behaviour, air permeability and stiffness properties were significantly influenced from the process types with different finishing substance ratios and from the weft yarn density as well as from the interaction of process type and weft yarn density at 0.05 significance level. Additionally, process type was a significant factor on water repellency of drapery samples however weft yarn density and the interaction of weft yarn density and the process type were not influential factors on water repellency at significance level of 0.05. For both warp and weft fabric directions, lowest damage zone at the length and width with the ignition source was obtained from the samples which were only treated with flame retardancy process without water repellency (90-0 coded process). The most satisfying results in terms of water repellency were obtained from the samples treated with 60-30 coded process where 60 g/l FR and 30 g/l water repellent chemical substances were utilized respectively. Drapery fabrics treated with 60-0 coded process revealed the best windproof feature indicating the lowest air permeability.